The effect of radial convection on cell proliferation Iin bone tissue engineering - Shao, Weiru (My University, 2009)
Large bone defects are frequently encountered during surgeries. Traditional methods of repair are limited by bone graft availability and increased surgical morbidity. Tissue engineered bone tissue has many clinical advantages. However, its current technology is limited by implant size and lacks of immediate nutritional perfusion once the tissue is implanted. Objective: To sustain cell growth and proliferation in a three-dimensional scaffold unit with radial convective flow. Material and Methods: Fetal rat calvarial cells were harvested and loaded into 1x1 cm hydroxyapatite cylinders. Microperforated hollow fibers were placed at the center of the cylinders to generate radial convective flow with oxygenated cell culture medium under hydraulic pressure. Live cell densities within the blocks were determined after 8 days of convection. Results: Radial convection sustained cell growth and proliferation better than simple diffusion at all three zones of the cylinders: center, outer, and rim. Conclusion: Radial convective flow is capable of supporting cellular function and proliferation in small scaffold units. The design of the radial convection units and their system parameters are validated by this study. The results are very useful to devise future tissue engineering studies involving radial convective flow.
University of Minnesota Ph.D. dissertation. May 2009. Major: Otolaryngology. Advisor:Steve Juhn, MD. Co-Advisor: Rick Odland, MD, PhD. 1 computer file (PDF); viii, 90 pages, appendix pages 49-51.
Keywords: Bone; Convection; Engineering; Hydroxyapatite; Radial; Tissue; Otolaryngology